Kebersihan Lingkungan Bersama Warga RT 21 RW 05 Kelurahan Betungan Kecamatan Selebar Kota Bengkulu - Afrizon, Jefri Julian; Yani, Satri; Muttaqien, Bimbim Alif; Alzen, Alzen; Nopransyah, Nopransyah; Lismana, Oetari; Martiani, Martiani; Sumantri, Ajis (Jurnal Karya Nyata Pengabdian, 2025)
The 2025 Dehasen Bengkulu University Community Service Program (KKN) was held in RT 21 RW 05, Betungan Village, Selebar District, Bengkulu City. The work program implemented during the KKN period is "GOTONG ROYONG (Cleaning the Village Environment)". This work program aims to examine how the role of solidarity works, of course supported by how the community responds to each value in mutual cooperation that is embedded in their environment. In this literature study method, which searches for databases from various references, such as research journals, journal reviews, and data related to the culture of mutual cooperation. From the results of the study, it can be concluded that in the mutual cooperation activities that have been carried out in RT 21 RW 05, Betungan Village, it can foster a sense of mutual help or togetherness among local residents that can be established well. Without us realizing it, this can strengthen/strengthen their sense of solidarity to continue to work together to maintain the culture and moral values contained in mutual cooperation activities.